Prediction of the unsteady ventilated partial cavities - Volodymyr Semenenko; Olena Naumova (Mechanics and Advanced Technologies, 2020)
Approximate methods of computing the unsteady ventilated partial cavities created on both the plane and the cylindrical streamlined surfaces have been developed. The cases of plane partial cavities past a slender wedge-shaped cavitator, and axisymmetric partial cavities past a ring flange on the surface of an infinite circular cylinder are considered. Results of computer simulation of the unsteady ventilated partial cavities of both that types are shown. A comparison of the unsteady behavior of plane and axisymmetric ventilated partial cavities is given. A comparative analysis of two methods of controlling the partial cavities by varying the cavitator shape and by regulating the gas supply rate into a cavity is given. It has been shown that the first method is more effective for a partial cavity on a plane. For an axisymmetric partial cavity on a cylinder, both the control methods appear ineffective.